An Assesment of ICT Availability, Utilizaton and Retention Challenges in Teaching Arabic Language in Kwara State Secondary Schools - Sanni Abdulhameed Muhammed; Abdul-Hamid Habibullahi; Muhammad Soliu Ibrahim Muhammad (Permata : Jurnal Pendidikan Agama Islam, 2025)
The integration of Information and Communication Technology (ICT) into education has become increasingly important for enhancing teaching effectiveness and learner engagement, particularly in language education. This study investigated the availability, utilisation, retention challenges, and instructional impact of ICT tools in the teaching of Arabic language in secondary schools in Kwara State. The primary purpose of the study was to assess how the sustained use of ICT tools influences instructional practices, students’ academic performance, and interest in Arabic language learning. A descriptive survey research design was adopted for the study. The population comprised Arabic language teachers and senior secondary school students in Kwara State, from which a sample of 200 respondents was selected using random sampling techniques. Data were collected using a structured questionnaire and analysed using mean scores and chi-square statistical tests. The findings revealed that ICT tools are largely unavailable and rarely utilised in Arabic language teaching across the sampled schools. However, both teachers and students strongly perceived ICT as effective in improving students’ comprehension, pronunciation, motivation, and academic performance in Arabic. Major challenges identified include unreliable electricity supply, lack of technical support, high maintenance costs, inadequate teacher training, and insufficient curricular support. The study concludes that while ICT has significant potential to enhance Arabic language teaching and learning, its impact is constrained by systemic and infrastructural challenges. The study contributes to existing literature by highlighting the importance of ICT retention and sustainability, rather than mere availability, in improving Arabic language education in secondary schools.